Barriers to, and facilitators of, the adoption of a sugar sweetened beverage tax to prevent non-communicable diseases in Uganda: a policy landscape analysis - Gemma Ahaibwe; Safura Abdool Karim; Anne-Marie Thow; Agnes Erzse; Karen Hofman (Taylor & Francis Group, 2021)
Background Uganda is experiencing an increase in nutrition-related non-communicable diseases. Risk factors include overconsumption of sugar-sweetened beverages. Fiscal and taxation policies aim to make the consumption of healthier foods easier. However, the adoption and implementation of fiscal policies by countries are constrained by political and economic challenges. Objective We investigated the policy and political landscape related to the prevention of nutrition-related non-communicable diseases in Uganda to identify barriers to and facilitators of the adoption of sugar-sweetened beverage taxation in Uganda. Methods A desk-based policy analysis of policies related to nutrition-related non-communicable diseases and sugar-sweetened beverage taxation was conducted. Four key informant consultations (n = 4) were conducted to verify the policy review and to gain further insight into the policy and stakeholder contexts. Analysis was framed by Kingdon's theory of agenda setting and policy change. Results Nutrition-related non-communicable diseases were recognised as an emerging problem in Uganda. The Government has adopted a comprehensive approach to improve diets, but implementation is slow. There is limited recognition of the consumption of sugar and sugar-sweetened beverages as a contributor to the nutrition-related non-communicable disease burden in policy documents. Existing taxes on soft drinks are lower than the World Health Organization's recommended rate of 20% and do not target sugar content. The soft drink industry has been influential in framing the taxation debate, and the Ministry of Finance previously reduced taxation of sugar-sweetened beverages. Maintaining competitiveness in a regional market is an important business strategy. However, the Ministry of Health and other public health actors in civil society have been successful (albeit marginally) in countering reductions in taxation, which are supported by industry. Conclusions An established platform for sugar-sweetened beverage taxation advocacy exists in Uganda. Compelling local research that explicitly links soft drink taxes to health goals is essential to advance sugar-sweetened beverage taxation.